PENGARUH KEBIJAKAN HARGA DAN PENGEMBANGAN DESAIN TERHADAP KEPUTUSAN PEMBELIAN TELEVISI MEREK SHARP PADA TOKO WANDHA ELEKTRONIK DI MUARA BADAK - MULIATI, MULIATI; PUTRI, EVA NORHYA AKHMAR RAMADHAN (I-Con Media, 2021)
The purpose of this study was to determine the effect of price policy and design development simultaneously and partially on the decision to purchase Sharp televisions at Wandha electronics store in Muara Badak, and to find out the most influential variable on the purchase decision of Sharp television at the Wandha electronics store in Muara Badak. The samples in this study were 30 respondents. The data analysis technique of this research was multiple regression, with hypothesis testing using the F test and t test. The results showed that simultaneously and partiallyl both of these variables, namely the price policy and design development significantly and positively influence the decision to purchase Sharp televisions at the Wandha Elektronik Store in Muara Badak. The most influential variable is the price policy.